The national and provincial burden of transport injuries in Iran between 1990 and 2021 - Amin Abbasi; Moloud Balafar; Mahboub Pouraghaei; Samad E.J. Golzari; Maryam Soleimanpour; Sajjad Ahmadi; Hassan Soleimanpour (Scientific Reports)
Abstract Transport injuries (TIs) are a major cause of mortality and morbidity worldwide, and Iran, with its rapid demographic transitions in recent decades, is no exception. This study aimed to assess the burden of TIs in Iran and its provinces from 1990 to 2021. Estimates from the Global Burden of Diseases (GBD) 2021 were used to report age-standardized rates (ASRs) for the prevalence, incidence, mortality, and disability-adjusted life years (DALYs) of TIs by sex, age group, injury type, province, and Socio-demographic Index (SDI). In 2021, Iran recorded 1.147 million (95% uncertainty interval (UI): 1.014 to 1.287 million) incident cases of TIs with an age-standardized incident rate of 1341.9 per 100,000 (95% UI: 1193.7 to 1495.1). Compared with 1990, its prevalence, incidence, death, and DALY rates decreased by − 52% (95% UI: − 54% to − 50%), − 52% (95% UI: − 55% to − 50%), − 62% (95% UI: − 65% to − 58%), and − 64% (95% UI: − 67% to − 61%), respectively. At the provincial level, Tehran (233.1; 95% UI: 191.3 to 304) had the lowest age-standardized DALY rate, while the highest DALY rate was for Sistan-Baluchistan (2155.3; 95% UI: 1866.2 to 2478.3). In addition, age-standardized DALY rates were mainly higher for males, the 20–24 age group, and provinces with a lower SDI. Despite a significant decrease in TIs in Iran since 1990, they still pose a significant burden, with notable disparities across provinces and demographic groups. Targeted prevention programs focusing on high-risk populations, such as young adults and lower-SDI provinces with lower SDI, are recommended.